2001
DOI: 10.1103/physrevlett.87.277902
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishability of Bell States

Abstract: More than two multipartite orthogonal states cannot always be discriminated if only local operations and classical communication (LOCC) are allowed. We show that four Bell states cannot be discriminated by LOCC, even probabilistically, using the separability properties of a four-party unlockable bound entangled state. Using an existing inequality among the measures of entanglement, we show that any three Bell states cannot be discriminated with certainty by LOCC. Exploiting the inequality, we calculate the dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
262
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(271 citation statements)
references
References 11 publications
8
262
1
Order By: Relevance
“…However, it has been proven that a complete BSM (distinguishing between the four states with 100% efficiency) is impossible using only linear operations and classical communication [8,9,10,11]. In fact, Ghosh et.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been proven that a complete BSM (distinguishing between the four states with 100% efficiency) is impossible using only linear operations and classical communication [8,9,10,11]. In fact, Ghosh et.…”
Section: Introductionmentioning
confidence: 99%
“…al. [11] have proven that, if only a single copy is provided, the best one can do is discriminate between two Bell states. Calsamiglia and Lütkenhaus [10] have shown that the maximum efficiency for a linear Bell-state analyzer is 50%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them considered the set with maximally entangled states [5][6][7][8][9][10][11][12][13][14], while the others aimed at the set with product states [2,[15][16][17][18][19][20][21][22][23][24][25][26]. Both of these researches can lead us a better understanding the limitation of the local operations and classical communication.…”
Section: Introductionmentioning
confidence: 99%
“…But any great circle of the Bloch sphere is of particular interest : (i) any great circle is the largest set of Bloch vectors that can be exactly flipped [18,19], and this fact can be used for remote (exact) state preparation [20], (ii) a product state of two parallel qubits and the corresponding product state of two antiparallel qubits contain equivalent information about the qubit, if the Bloch vectors of all these qubits lie on the same great circle [21], (iii) the optimal universal 1 → 2 (isotropic) cloning machine of the equator (on which the states |0 , |1 , (1/ √ 2)(|0 ±|1 ) lie) is the same as that of the set {|0 , |1 , (1/ √ 2)(|0 ±|1 )} [22]. We consider here the set of all entangled states, where all the Bloch vectors of the reduced density matrices of one side lie on the disc of a great circle.…”
mentioning
confidence: 99%